Fowl Cholera and Its Control Prospect With Locally isolated Pasteurella multocida Bivalent Vaccines - Ariyanti, Tati; ., Supar (Indonesian Animal Sciences Society, 2008)
Pasteurellosis or fowl cholera disease which associated with Pasteurella multocida group A and D infections occurred sporadically in many parts of the world, including in Indonesia. The pathogenic activity of P. multocida in chickens were based on lipopolysacharide (LPS) antigens associated with group A and D capsules, and the resistance factor of complement mediated bacteriolysis in animals. In order to reduce common bacterial infections, antibiotics were routinely used as feed additive or by drinking water, but fowl cholera cases still occur. Fowl cholera control by vaccinations have been used more than a hundred years ago by means of inactive vaccine, but imported inactive vaccine was reported not effective due to lack of cross protection against heterologous serotype. At present, manyÂ local P. multocida isolates from chicken and ducks from manyÂ areas in Indonesia were characterised for their antigenicity, immunogenicity and prepared as monovalent or bivalent vaccine. Only the monovalent vaccine prepared from BCC 2331 or DY2 demonstrated the presence of immunoprotection against homologous and heterologous challenged with live bacteria. The prototype bivalent vaccine consisting of BCC 2331 + DY2 demonstrated high degree of cross protection against challenged individual with or mixed of BCC 2331 + DY2 at average of 60 â 75% and 75 â 100%, respectively. Monovalent and bivalent vaccine prepared from other isolates including imported reference strains of P. multocida demonstrated no protection in experimentally vaccinated ducks and chicken against challenged with live bacteria of neither BCC 2331 nor with DY2. From these retrospective studies, it was concluded that the local isolates P. multocida designated Â as Â BCC Â 2331 Â and Â DY2 Â could Â be Â used Â as candidates Â of Â prototype Â vaccine Â or Â master Â seed Â vaccine Â but their effectiveness still need to be evaluated under field conditions.Â Key words: Pasteurella multocida, Indonesian isolates, inactive vaccines, fowl cholera